Limites e possibilidades do uso de sistemas de informações: análise de dados sobre violência por orientação sexual e identidade de gênero no estado do Ceará - Oliveira, Fernando Virgílio Albuquerque de (2024)
Violence against the Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, Asexual, and more (LGBTQIA+) population, or LGBTQIA+phobic violence, is a serious public health issue in Brazil and Ceará. The objective of this study was to understand the limits and possibilities of using multisectoral information systems on violence based on sexual orientation and gender identity in the State of Ceará, mapping public policies, identifying data-generating institutions, characterizing the informative profile of information sources, integrating databases, and describing victimization data. This is a cross-sectional, analytical, quali-quantitative study with a mixed approach, using primary and secondary data in four stages. The first stage involved a documentary study of official legislation and norms from 2001 to 2022; the second stage consisted of semi-structured interviews and discussions with two groups of key informants from the health, education, security, and human rights sectors, using snowball sampling: GIC1 comprised 14 authorities from official institutions producing interpersonal violence data in Ceará and GIC2 comprised 10 managers and professionals from institutions managing public policies related to these data; the third stage analyzed the potential for probabilistic integration of databases divided into GBD1 (database with relationship variables for integration, including the Mortality Information System and Notifiable Disease Information System) and GBD2 (databases without integration potential, including Intentional Violent Crimes, Sexual Crimes, Suicides, and the National Human Rights Ombudsman's data panel); finally, the fourth stage characterized the population profile. The analysis of stages 1 and 2 included content analysis (using ATLAS.ti 23.1.2 software), while stages 3 and 4 used linkage (using Python language) and descriptive statistics (Stata® software version 11.2). The study was approved by the CEP/UFC (Opinion 4.864.116). The main sources identified were the health, security, and human rights sectors, with the latter two being more recent in population data monitoring. The main limitation identified was the lack of information on gender identity (39.1% in health; 99.7% in public security; and 71.9% in human rights). Opportunities were observed in the process of consolidating systems and expanding policies for monitoring and addressing grievances, such as criminalizing homophobia and transphobia, alongside the efforts of local social movements for implementation and assurance. Data from GBD1 revealed a higher proportion of firearm homicides (31.5%), while GBD2 showed that most victims were transgender women and travestis (health: 30.9%; security: 42.9%; human rights: 8.4%) or homosexuals (health: 61.9%; security: 52.4%; human rights: 36.5%), with low educational attainment (health: 24.8% incomplete elementary; security: 21.4% literate; human rights: 7.2% incomplete secondary). There was statistical significance between gender identity and sexual orientation with the year in Sinan (both associations presenting p<0.001) and with the type of Intentional Violent Crimes (p=0.002 and p<0.001, respectively). It is concluded that the main limitations of information systems on violence against the population in Ceará are low completeness of important variables and weaknesses in data collection, while possibilities lie in improving consolidating systems and policies for continuous monitoring.